“Resolving difficult cases that might happen during Divine Service”. On the sources of one plot in the Uniate liturgical literature of the early 17th century - Margarita Korzo (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2022)
The article analyzes the Latin Sources of an admonition “Pripadkov kotorye byse pry slouzhbie bozhoi mogly prytrafiti roz’viezane” (Resolving difficult cases that might happen during worship). Published for the first time as a part of a larger Uniate manual for the priests in Sluzhebnik (Vilno 1617), the given admonition in an edited form became an organic component of the so-called “Izvestie uchitel’noe, kako dolzhenstvuet iereyu i diakonu sluzhenie w tserkvi svyatoi sovershati” (Instructive admonition how a priest and deacon should perform holy service in the church) in the Russian Rituals. As A.V. Petrovskij has already found out, a significant part of the cases analyzed in “Pripadki” that might happen during worship or Communion have parallels in apostolic, patristic, and conciliar decrees, in works of church literature, which have long existed in the Eastern Christian area. The author of the article argues, that the very effort of systematizing those difficult cases, also their analysis in the context of liturgical editions was borrowed by the compilers of “Pripadki” from the Latin tradition. And the main sources were the headings (rubricae) of the post-Tridentine “Missale Romanum” (Rome 1570). “Summa casuum conscientiae” by the Spanish Jesuit, cardinal Francisco de Toledo became another important source for the Uniate compilation: both for “Pripadki”, as for the whole Uniate manual for the priests Vilna 1617. Familiarity of the Uniate compilers with the work of the Spanish Jesuit is also confirmed by the content of another work, namely – an instruction for the priests how to perform the sacraments in “Trebnik” (Vilna 1617–1618). The given fact allows us to consider both admonitions as a part of a broader program for the elaboration of practical manuals for the Uniate clergy at the beginning of the 17th Century. The article also suggests who could be the author of these compilations